Investigación en cacao convenio ICA - SENA - Comité de Cafeteros de Santander :granja Aguas Calientes el Playón - Morales G., Jaime; Garzón G., Diego (Compañía Nacional de Chocolates, 2018)
Bark Canker on Cocoa, caused by -Phytophthora spp., has been reported in great part of cocoa areas growed in Colombia. Traditionally, control of bark canker has been effectuated by excision of diseased tissue but nowadays it was replaced by :scraping away the bark over and around the canker followed by painting with a 0.25 per cent Metalaxyl fungicide. It was confirmed the healing effects of Metalaxyl on diseased tissue which was better when applied on small canker.